Business Simulation Training Using Monsoonsim - Yuwono Marta Dinata; Christian Tanjono; Rinabi Tanamal; Evan Tanuwijaya (LPPM Universitas Muhammadiyah Tasikmalaya, 2021)
Business simulation training has been conducted by the School of Information Technology, Information Systems Department, Ciputra University, using MonsoonSIM. The aim of this activity is to introduce the concept of Enterprise Resource Planning (ERP) to students through virtual business simulation game. This training was conducted online, due to to Covid-19 pandemic. By using MonsoonSIM software, students can manage a virtual company and learn the company's business processes. Learnings in this training were in the form of material module explanations, simulations, discussions, and evaluations. This program was attended by students from Junior High School and Senior High School. Participants not only play individually to learn from the game experience, but also in a team to compete to be the best virtual company that can dominate the market within a predetermined period of time. By participating in this training, students can manage the operational processes of a virtual company, understand existing resources, and can make a company planning strategy in order to survive and grow.